Novel HDAC/Tubulin Dual Inhibitor: Design, Synthesis and Docking Studies of α-Phthalimido-Chalcone Hybrids as Potential Anticancer Agents with Apoptosis-Inducing Activity - Mourad AAE; Mourad MAE; Jones PG (Dove Medical Press, 2020)
Ahmed A E Mourad,1 Mai A E Mourad,2 Peter G Jones3 1Pharmacology and Toxicology Department, Faculty of Pharmacy, Port-Said University, Port-Said, Egypt; 2Medicinal Chemistry Department, Faculty of Pharmacy, Port-Said University, Port-Said, Egypt; 3Institute of Inorganic and Analytical Chemistry, Braunschweig, GermanyCorrespondence: Ahmed A E Mourad Tel +201069233766Email ahmed.mourad@yahoo.comIntroduction: In order to develop novel anticancer HDAC/tubulin dual inhibitors, a novel series of α-phthalimido-substituted chalcones-based hybrids was synthesized and characterized by IR, 1H NMR, 13C NMR, mass spectroscopy and X-ray analysis.Methods: All the synthesized compounds were evaluated for their in vitro anticancer activity against MCF-7 and HepG2 human cancer cell lines using MTT assay. To explore the mechanism of action of the synthesized compounds, in vitro β-tubulin polymerization and HDAC 1 and 2 inhibitory activity were measured for the most potent anticancer hybrids. Further, cell cycle analysis was also evaluated.Results: The trimethoxy derivative 7j showed the most potent anticancer activity, possessed the most potent β-tubulin polymerase and HDAC 1 and 2 inhibitory activity and efficiently induced cell cycle arrest at both G2/M and preG1phases in the MCF-7 cell line.Keywords: chalcones, α-phthalimido, anticancer, cell cycle, histone deacetylase inhibitor, tubulin polymerase inhibitor